Board members, corporate social responsiveness and profitability: Are tradeoffs necessary? - O'Neill, Hugh M. (Journal of business ethics, 1989)
The relationship between corporate social responsiveness and profitability is investigated in a sample of corporate directors. The findings show there is no relationship between the level of director social responsiveness and corporate profitability. The implications of these results are discussed, especially as they relate to concerns about corporate governance.